Need and Importance of Medical Social Work Practice in Pakistan with Special Reference to Karachi City - Riaz, Sakina; Sarfaraz, Syeda Farhana (Advances in Social Sciences Research Journal, 2015)
In this research paper, the researcher has attempted to define the medical social work philosophy and tried to relate with social caring obligation and value system of Pakistani people. This paper examines the development of social work with special reference to Pakistan. The main purpose of this paper is to understand how Medical social work is designed and implemented in Pakistan? What are the challenges and what are the administrative problems faced by professionals? The paper is divided into three sections, section 1) provides a brief introduction of social work education in Pakistan, section 2) cover the history of the profession with special reference to Pakistani pedagogies and 3) discuss the role of Medical social worker in the context of Pakistan. The succeeding portion covers the conclusion and recommendation. An attempt has been made for in-depth analysis of the various aspects of existing practices; identify the problems and prospects of Medical Social Work with especial reference to Karachi, an urban city of Pakistan. This study is an exploratory research and researcher employing qualitative methods to explore this issue.